Optimizing GaxOy Growth Tendency of 3D Structures on Different Substrates through the MOCVD Technique. (16th July 2019) - Yaseen, Maria; Nunes, Frederico D.; Sacciloti, Marco; Lins, Emery C.
Abstract : The main purpose of this study was to optimize the GaxOy growth on different substrates surfaces under constant deposition temperature. Metallic gallium in liquid form was successfully deposited on Ti alloy, Silicon and Sapphire substrates by using metallorganic chemical deposition technique. It resulted in microspherical-shaped liquid gallium (GaxOy) just by adjusting the deposition parameters such as temperature, partial pressure and time. For these results, oxygen was not properly provided during the deposition. SEM, XRD, PL (photoluminescence) and XPS techniques featured the morphology and structure of the samples "as-deposited". The growth at 650°C resulted in randomly distributed GaxOy microspheres with the diameter ranging between 80nm and 200nm and amorphous or polycrystalline phase. Peaks of the PL spectra at 420nm (Ti alloy), 480nm (Si) and 410nm (Sapphire) revealed oxygen-based defects in the deposition layer. Further, XPS confirmed the presence of Ga and oxygen with specific binging energy and atomic concentration.